THE ROLE OF THE STATE IN THE INTERNET-MEDIATED INFORMATION AND COMMUNICATION ENVIRONMENT - Mitrović, Marta; Vujović, Marija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The development of the Internet and the so-called erasing of national borders are constantly provoking the role of the state in the new information and communications environment. While, on the one hand, the state is challenged by its former power, which it drew from the exclusivity of its territoriality, on the other hand, the role of the state can be seen as changed, but not insignificant. Numerous examples in the past decade testify to the fact that the state still has the power to control its Internet-mediated information and communications environment. Conceptual changes were necessary to respond to the modern times - the term system has been replaced with the term environment; it is more about management than strict control through regulation - however, the role of the state, although changed, remains central in the new environment as well. The aim of this paper is to answer the research question: How has the role of the state changed in the new information and communications environment?
Keywords: state; information and communications environment; internet; (self)regulation; system